California Strawberry Consumption Alters Gut Microbiome in Healthy Participants: A Pilot Study. (29th May 2020) - Henning, Susanne; Yang, Jieping; Woo, Shih Lung; Li, Ru-Po; Huang, Jianjun; Thames, Gail; Gilbuena, Irene; Tseng, Chi-Hong; Ezzat-Zadeh, Zahra; Heber, David; Li, Zhaoping
Abstract: Objectives: Based on the polyphenol and fiber content of strawberries (SB), it was our hypothesis that daily consumption of California strawberries will lead to changes in the composition of the intestinal microbiota, and concentration of fecal cholesterol and bile acid (BA) microbial metabolites. Methods: We performed a randomized, double blind, parallel design intervention study. 28 healthy adults were randomized to either daily consumption of 26 g of SB powder (2 servings of fresh SB) or placebo (PL) powder for 4 wks. Stool samples were collected at baseline (BL), 4 and 6 wks (2 wks no SB/PL). Fecal microbiota was analyzed by 16S rDNA sequencing of the V4 region; fecal cholesterol, coprostanol, cholestanol, cholic acid (primary BA), chenodeoxycholic acid (primary BA), deoxycholic acid (2 nd BA), lithocholic acid (2 nd BA) by gas chromatography, serum cholesterol, triglyceride by colorimetric assay and serum pelargonidin glucuronide (PG) by high performance liquid chromatography. Results: Serum PG, a SB anthocyanin, was found in all participants in the SB group. Two participants in the PL group showed serum PG and were excluded from the analyses. Daily SB increased the abundance of Christensenellaceae, Bifidobacteriaceae, Verrucomicrobiaceae and multiple members of the Lachnospiraceae, Ruminococcaceae family, and decreased significantly Alcaligenaceae/Sutterella comparing BL to wk4. Comparing the change from BL to wk4 between the SB and PL group, we found increased abundance of Alcaligenaceae/Sutterella and several members of the Clostridia class including Lachnopsiraceae and Ruminococcaceae and a decrease in Clostridiaceae. Comparing wk 4 to wk 6, we observed a reversal of Clostridiales/Christensenellaceae, Verrucomicrobiaceae, and Alcaligenaceae/Sutterella. No effects on alpha and beta diversity were observed. No significant difference in serum and fecal cholesterol, BA and bacterial metabolites was observed between SB and PL groups. Five participants did not form coprostanol. Comparing coprostanol producers to non-producers at baseline showed that most differences were observed in the Lachnospiraceae, Ruminococcaceae and Bacteroidaceae families. Conclusions: SB consumption altered the gut microbiota, which was partially reversed after 2 wks of customary diet without SB. Funding Sources: California Strawberry Commission.